Campbell Island Teal: conservation update - Gummer, H; Williams, M (Wildfowl, 1999)
The single surviving wild population of Campbell Island Teal, restricted to Dent Island in the New Zealand subantarctic, is unlikely to exceed 25 pairs. Twelve Campbell Island Teal were released in 1999 onto Codfish Island in southern New Zealand to establish, temporarily, a second wild population. These birds originated from a captive breeding programme that has produced 40 fledglings during 1994 - 1998 from an initial wild-caught stock of 11 birds. Wild-raised and wild- acclimatised teal from Codfish Island are intended as the source for eventual re-establishment on Campbell Island. Planning for the removal of Norway rats, the sole remaining alien mammal there, has commenced.